Derivations from Law 13.010: Women's Political Rights in the Provinces - Barry, Carolina (Centro de Estudios Avanzados, 2016)
Between 1947 and 1951, Perón's government produced a reformist movement that implemented a set of legal instruments through which electoral mechanisms and practices were radically modified. One of them was Law 13.010 on women's political rights. Once it was enacted, and in order not to be distorted, it was necessary to have similar legislation in the provinces, at a time when the right to vote did not have constitutional reception at the national level, which would give them a wide margin of action, either through their norms or their constitutions. This article synthesizes this process of provincial derivations and adaptations of the women's suffrage law.Translated with www.DeepL.com/Translator